Effect of Row Spacing on Yield, Yield Components and Crude Oil of Autumn and Spring Sowed Mustard (Sinapis arvensis L.) in Eight Locations of Turkey - Fatma Kayaçetin; Güngör Yılmaz; Fadul Önemli; Ahmet Kınay; Mehmet Niyazi Kıvılcım; Arzu Köse; Halil Hatipoğlu; Nimet Kara; Fırat Sefaoğlu (Journal of Agricultural Sciences)
This study was conducted to evaluate the effect of autumn and spring sowing and row spacings (20, 30, 40, 50 and 60 cm) on yield, yield components and crude oil percentage of mustard (Sinapis arvensis L.) at eight locations lying in different ecological zones (Ankara, Aydın, Erzurum, Eskişehir, Isparta, Şanlıurfa, Tekirdağ and Tokat) during 2013-14 and 2014-15 growing seasons. The experiment was designed according to the “Split Plots on Randomized Complete Block” with four replications. Autumn and spring sowing were main plots, row spacings were sub-plots in each location. The results showed that, autumn and spring sowing and row spacing significantly affected yield, yield components and crude oil yield across locations. In general, increasing row spacing reduced seed yield and crude oil percentage. The plants from autumn sowing increased crude oil yield compared to the plants from spring sowing. The maximum seed yield and crude oil yield (2525.5 and 695.3 kg ha-1, respectively) was obtained from Tokat during autumn sowing at 50 cm row spacing. It was determined that autumn sowing was more suitable for Aydın, Tekirdağ, Tokat and Şanlıurfa locations. Autumn sowing could also be possible at Ankara, Eskişehir and Isparta locations if plants enter to winter at the right time (8-10 leaves rosette stage). Agronomic performances of mustard at Erzurum was not promising. For autumn and spring sowing, the most suitable row spacing must be 20-30 cm in Ankara, Aydın, Erzurum, Eskişehir, Isparta, Tekirdağ and Şanlıurfa; 50 cm in Tokat in autumn sowing.